Independent validation and regulatory agency approval for high rate algal ponds to treat wastewater from rural communities. Issue 2 (16th November 2017) - Fallowfield, Howard J.; Young, Paul; Taylor, Michael J.; Buchanan, Neil; Cromar, Nancy; Keegan, Alex; Monis, Paul
Abstract : This is the first validation of a HRAP accepted by a regulatory agency and resulted in the system being incorporated into the South Australian Community Wastewater Management Scheme – as depicted. Abstract : Despite the many recognised benefits, the application of high rate algal ponds (HRAP) to manage wastewater treatment in small communities has been limited. To be incorporated into the South Australian Community Wastewater Management Scheme (CWMS), new wastewater treatment systems are required to undergo validation and obtain regulatory approval from the South Australian Department of Health, Wastewater Management Group. A HRAP system at Kingston on Murray, South Australia, underwent validation to be incorporated into the CWMS. The process was consistent with the Australian National Guidelines which requires the demonstration of the log10 reduction values (LRV) for indicator organisms achieved by the wastewater treatment system. These were required to be measured twice weekly, over a 10 week period in below average solar radiation and temperature conditions, by an independent National Association of Testing Authorities accredited laboratory. The Australian Water Quality Centre was commissioned to assess the removal of Escherichia coli, F-RNA bacteriophage and aerobic spore-forming bacteria. Flinders University of South Australia concurrently monitored the removal of the same organisms and other standard wastewater parameters. While ASFB were shown to be unsuitable indicators of protozoa in natural pond systems, the system effectively removed E. coli and F-RNA bacteriophage with the treated effluent meeting the limits set by the guidelines for effluent reuse for non-food crop irrigation: a 5th percentile LRV of >1.0 for F-RNA bacteriophage and a median E. coli concentration of <4.0 log10 E. coli MPN 100 mL −1 . Based on these results two configurations of HRAP systems were approved to be incorporated into the CWMS.